Historical and theoretical justification of Movement of non-alignment - I. I. Pavlov (Vestnik MGIMO-Universiteta)
In the article the author draws attention to the subject of the Non-Aligned Movement, examines key periods of its evolvement as well as compares various points of view on the role and place of the Non-Aligned Movement in the contemporary world. More importantly, the author regards as one of the crucial problems the question of a further organization's development within the confines of current international relations; as well as analyses following transformation of its goals and aims in response to the threats of the changing world.